Answer:
M = 3.485 kg
m = 1.605 kg
Step-by-step explanation:
F = 0.98 x 10^-8 N
r = 19.5 cm = 0.195 m
M + m = 5.09 kg ...... (1)
By use of Newton's gravitational law
F = G m1 m2 / r^2
0.98 x 10^-8 = 6.67 x 10^-11 x M x m / (0.195)^2
M x m = 5.59
![M - m = \sqrt{(M + m)^(2)-4 M m}](https://img.qammunity.org/2020/formulas/physics/college/3ojj5399245era915jz61eq4ov42b265jt.png)
![M - m = \sqrt{(5.09)^(2)-4 * 5.59}](https://img.qammunity.org/2020/formulas/physics/college/ivhnw8cu6qr5jzj4hs90svvphhvyloifg7.png)
M - m = 1.88 .........(2)
By solving the equation (1) and equation (20, we get
M = 3.485 kg
m = 1.605 kg